Critical current density and vortex pinning mechanism of Lix(NH3)yFe2Te1.2Se0.8 single crystals. (29th September 2017) - Wang, Shaohua; Sun, Shanshan; Lei, Hechang
Abstract: We grew Li x (NH3 ) y Fe2 Te 1.2 Se 0.8 single crystals successfully using the low-temperature ammonothermal method, and the onset superconducting transition temperature T c onset is increased to 21 K compared to 14 K in the parent compound FeTe 0.6 Se 0.4 . The derived critical current density J c increases remarkably to 2.6 × 10 5 A/cm 2 at 2 K. Further analysis indicates that the dominant pinning mechanism in Li x (NH3 ) y Fe2 Te 1.2 Se 0.8 single crystal is the interaction between vortex and surface-like defects with normal core, by variations in the charge-carrier mean free path l near the defects ( δ l pinning). Moreover, flux creep is important to the vortex dynamics of this material.